How do colleges and universities respond to Covid-19: The experience of Chengdu Sport University - Kan, M.; Zhou, J. (Asia Pacific Journal of Public Health, 2020)
Since the outbreak of Covid-19 infectious pneumonia in Wuhan, China, in January 2019, it has rapidly spread to 31 provinces (autonomous regions and municipalities) across the country within 3 months. Chengdu Sport University is the only physical education institution in Southwest China. During the epidemic period, the university actively responded to the call of the government and issued response measures as soon as possible to achieve the goal of zero infection among teachers and students. This article describes in detail how to deal with the new coronavirus in colleges and universities during the epidemic.